Familial dilated cardiomyopathy in the United Kingdom. Issue 5 (May 1995) - Keeling, P. J.; Gang, Y.; Smith, G.; Seo, H.; Bent, S. E.; Murday, V.; Caforio, A. L.; McKenna, W. J.
Abstract : OBJECTIVES--To determine the frequency and mode of inheritance of familial dilated cardiomyopathy in the United Kingdom. BACKGROUND--Two recent prospective studies have suggested that familial forms of dilated cardiomyopathy are common but have been limited by selective screening methods, inadequate diagnostic criteria, and low rates of ascertainment. METHODS--Prospective screening study of 236 relatives from 40 families of patients with dilated cardiomyopathy. Screening consisted of clinical examination, 12 lead electrocardiogram, and two-dimensional Doppler echocardiography. Relatives with systemic hypertension and other cardiac diseases were excluded from the study. All echocardiograms were performed by an experienced echocardiographer who was blinded to clinical information. Relatives were classified as having dilated cardiomyopathy, left ventricular enlargement (method of Henry), depressed fractional shortening, or as being normal. Relatives with abnormal investigations underwent further evaluation as appropriate. RESULTS--Twenty five cases of dilated cardiomyopathy were identified and came from 10 (25%) of the 40 families screened. Pedigree analysis was most consistent with autosomal dominant inheritance and variable penetrance (65-95%). Of the remaining apparently healthy relatives, 37 (18%) were found to have left ventricular enlargement and nine (4%) depressed fractional shortening; these values were significantly higher than those observed in 239 healthy controls (24 (10%), P = 0.02 and one (0.4%), P = 0.01, respectively). CONCLUSIONS--Patients with dilated cardiomyopathy commonly have an affected family member and a high proportion of apparently healthy relatives with minor echocardiographic abnormalities. Segregation analysis suggests that familial dilated cardiomyopathy is the result of the transmission of a rare autosomal dominant gene. Further studies are currently underway to characterise the molecular basis of familial dilated cardiomyopathy and identify early disease within these families.